UV-B radiation suppresses chlorophyll fluorescence, photosynthetic pigment and antioxidant systems of two key species in soil crusts from the Tengger Desert, China. (February 2015) - Hui, Rong; Li, Xinrong; Zhao, Ruiming; Liu, Lichao; Gao, Yanhong; Wei, Yongping
Abstract: Field studies were conducted to investigate the influence of ultraviolet-B (UV-B) radiation on the moss Bryum argenteum and cyanobacterium Microcoleus vaginatus isolated from biological soil crusts (BSC) from the southeastern fringe of the Tengger Desert, China. UV-B supplementation with 0.33, 0.50, and 0.66 W m −2 was achieved using fluorescence tube systems for 40 days. We investigated Chl fluorescence parameters as well as photosynthetic pigment contents. We also measured lipid peroxidative production, malondialdehyde (MDA), superoxide dismutase (SOD) and catalase (CAT) which quench free radicals and prevent oxidative stress. We found that higher UV-B radiation significantly decreased ( p < 0.05) the Chl fluorescence parameters, Chl and carotenoid (Car) contents, and antioxidative enzymes activities. In addition, higher intensities of UV-B radiation induced dramatic increases in MDA content of B. argenteum and M. vaginatus . The results of this study showed that increased levels of UV-B radiation caused detrimental effects on chlorophyll (Chl) fluorescence, photosynthetic pigment and antioxidant systems of B. argenteum and M. vaginatus . B. argenteum was more sensitive to enhanced UV-B radiation than M. vaginatus . Increased UV-B intensity causes changes in the composition and structure of BSC that could impair their protective ecological functions in desert areas. Highlights: Bryum argenteum and Microcoleus vaginatus isolated from biological soil crusts were investigated. Photosynthetic performance and antioxidative enzymes activities were reduced by UV-B. Higher levels of UV-B radiation induced MDA accumulation. B. argenteum was more sensitivity to enhanced UV-B radiation than M. vaginatus.